Green synthesis and characterization of Triphala SiO2 nanoparticles and screening the efficacy on growth and biochemical constituents in Vigna radiata - Dhanushwr Kumar; Ranjani Soundhararajan; Hemalatha Srinivasan (Discover Nano)
Abstract The agricultural sector faces numerous challenges because of chemical fertilizers. Overuse of chemicals results in soil degradation, water and environmental pollution, potential health risks in all living forms on the earth. Chemical fertilizers adversely affects the soil microbes, deteriorating soil quality by nutritional deficits, hence necessitating eco-friendly alternatives for fostering crop growth. Nanotechnology provides innovative solutions, impacting every stage from seed germination to storage, promoting sustainable farming practices. Among these advancements, silica nanoparticles (SiNp) have emerged as a promising candidate for enhancing plant growth and development. To explore this potential, we report a novel green synthesis of Triphala medited silica nanoparticles (TpSiNps) by using aqueous fruit extract from a blend of Terminalia bellirica, Emblica officinalis, and Terminalia chebula fruits (Triphala), marking the first green synthesis of silica nanoparticles using a polyherbal formulation. The synthesized TpSiNps were characterized as stable, heterogeneous, and nano-coarse. Vigna radiata, a widely cultivated and nutritionally rich legume of agricultural significance, posed as a plant model to evaluate the potential of TpSiNps in promoting plant growth. Seedlings were treated with TpSiNps (1 ppm, 5 ppm, and 10 ppm) and analysed for seed germination, growth, and biochemical constituents. Experimental findings indicate that at 10 ppm, TpSiNps improved seed germination by ~ 45% and enhanced growth parameters, with shoot length by ~ 107%, root length by ~ 58%, and fresh biomass by ~ 59% in tested Vigna radiata. Furthermore, increased levels of bio constituents, including carbohydrates (~ 21%), proteins (~ 8%), tryptophan (~ 10%), chlorophyll (~ 8%), and carotenoids (~ 12%) suggest a stimulatory effect of TpSiNps on the metabolic processes of Vigna radiata. These results highlight TpSiNps's potential as a viable green nanotechnology solution for addressing agricultural challenges and ensuring food security.